Pitfalls of Impulse Purchase: A Case Study in Saudi Arabian Context (Global Journal of Management and Business Research, 2016)
The present study about pitfalls of impulse purchase has been carried out from customers' stand point of view. The study intends to educate and to create awareness among those class and category of customers who surreptitiously fall prey of lucrative packages and offers of products marketed and merchandised in super/hypermarket and malls. The present research intends to create awareness among customers who hardly give priority to the inherent worth and durability of goods and services provided by the dazzling and mind blowing slogans. There are certain class and category of buyers identified and located by the expert or analysts and managerial apparatus of impulse purchase -offer lucrative products and slogans in order to give boost and fulfill their sales target. Furthermore, the promises mentioned in products' features are just a violation of the basic agreement either partially: in quality or in other characteristics.
Keywords: customer awareness; floor display; merchandising; pitfalls of impulse purchase; window display